An endemic predaceous water beetle from the Murchison River in Western Australia—Antiporus kalbarriensis sp.n. (Coleoptera: Dytiscidae, Hydroporinae, Hydroporini) - Hendrich, Lars; Watts, Chris H. S. (Zootaxa, 2010)
Antiporus kalbarriensis sp.n. is described from the Murchison bioregion in Western Australia. The species appears to be restricted to backwater pools and oxbows along the Murchison River. Morphologically it is near Antiporus bakewellii (Clark, 1862) (Queensland, New South Wales), A. jenniferae Watts, 1997 (Northern Territory, N Queensland, NW Australia) and A. simplex Watts, 1978 (Queensland) but differs by the form of the median lobe, size and male proclaw. The habitat and its water beetle coenosis are described in detail. Additional distributional records for A. bakewellii and A. jenniferae are given. Altogether 15 species of Antiporus are now reported from Australia. The new species underline the importance of south-western Australia as a hotspot of diversity for Dytiscidae of the tribe Hydroporini Aubé, 1836.